Parish – an (Un)usual Place of Growing in Faith and Brotherhood. Twenty Years of the Existence of Matka Boża Wspomożycielka Wiernych Parish in Olsztyn - Rozen, Barbara (Studia Warmińskie, 2013)
The article was written due to the 20th anniversary of the founding of this Catholic parish in Olsztyn – Likusy. It is one of the small parishes in the local Church but at the same time it is distinct and unique as any living organism in a human being. Is it possible to experience the presence of God and His love in this parish? Is it the parish for our times? The author brings closer the history of the parish and its spiritual dynamics of life, comes to conclusions which forecast further trends of its development.